Participation in BRAC's Rural Development Programme and the impact of group dynamics on individual outcomes - Mahmud, Simeen; Huda, Samiha (BRAC, 2019)
This study explored women's participation in Brae's rural development programme to identify some unobserved selecting factors that are believed to influence women's decision to participate or not and, the effect of group dynamics on individual outcomes of women programme participants. The data used for the study originates from Brac-ICDDR, B Joint research project in Matlab (April-Aug. '95). Ever married women aged between 15-50 years in 2,241 households of 14 villages with Brae interventions were included in the study. The results show that women's decision to participate was determined significantly by reported health status, perceived contribution to household income, household land ownership, relation with husband and unwanted pregnancy. The individual factors like age, literacy, marital status, etc. had no effect on the decision to participate. Group dynamics was captured by three indexes e.g., VO (village organization) homogeneity, VO activity and VO social awareness. Of these, VO homogeneity appeared to have the most consistent and positive effects on mobility, · income-earning and modern family planning use. There were cross-cutting effects of the other two indexes on outcomes. From the findings, it is desirable to pay greater attention to group mobilisation and group formation processes in programme implementation.